Mandibular simple bone cysts: clinical case report - Silva, Daiany de Mendonça (2023)
Introduction: The simple bone cyst, also known as traumatic bone cyst, is a non-neoplastic lesion that most frequently affects regions of the body and mandible symphysis. It is an asymptomatic lesion that is commonly discovered through routine radiographic examinations, where it presents as a well-defined unilocular radiolucent image by a thin layer of loose connective tissue, without an epithelial lining. Objective: his study aimed to define a clinical case of a simple bone cyst which was treated in an effective and minimally invasive way. Clinical case report: A 22-year-old patient, Caucasian, female, looked for a dental care routine radiographic examination without symptomatic complaints. A hypodense image suggestive of a simple bone cyst was found through imaging exams. The treatment was proposed to perform surgery to curettage the cavity, with the aim of promoting bone neoformation. Conclusion: The tissue from the curettage was sent for histopathological analysis, and the result was compatible with the diagnosis of simple bone cyst. The patient is under radiographic follow-up with signs of bone neoformation and resolution of the clinical picture.